ANALYTICAL METHOD FOR ELASTIC RECOVERY PREDICTION OF AIR BENDING SHEET - Gonzalez-Coneo, Jorge; Gonzalez-Olier, Camilo; Pedraza-Yepes, Cristian; Higuera-Cobos, Oscar; Troncoso-Palacio, Alexander (Journal of Applied Engineering Science, 2023)
The estimation of the elastic recovery is of great importance during the planning of plastic deformation processes, because this estimation could reduce the number of required steps to reach the target geometry. The sheet bending process is one of the most widely used industrial processes, and that is why this paper seeks to provide an analytical model based on an elastic behavior with potential hardening of the material that could be combined with the geometric information of the process to estimate the degree of recovery of the components. The potential hardening model was selected due to its simplicity and good fit with the experimental data observed in steel sheets in this application. The effectiveness of the model was compared with the results obtained by several authors. The effectiveness of the model is significantly influenced by the parameters of the bending process and the method used to estimate the radius of curvature.